Inclusive education in the Chilean educational reality - Vásquez Burgos, Karina (2017)
The present theoretical revision aims to present the current Chilean reality about curricular change, which points to an inclusive vision of education.This study was carried out by means of a bibliographical review of the context in which Chilean educationand its relation with Special Educational Needs are found, through an educational analysis of the legislation and the educational curriculum, highlighting fundamental aspects about a methodological structure Diversifies. It concludes with a view on the change in legislation and factors that are relevant to a diversified, inclusive education for all students.